(untitled) (Research, Society and Development, 2020)
This study aimed to investigate whether there is a relation, as well as its configuration, between the dissatisfaction with body image and the occurrence of disordered eating behaviors in undergraduate female students. For this purpose, an integrative review was conducted in the Lilacs, Scielo, PMC and PubMed indexed databases in January and February 2019, by means of DeCS and BVL terms: feeding/ eating behavior, college/ university students, body dissatisfaction, and eating habits. The search resulted in 433 references with a final sample of 21 articles, which underwent summarization, and evidenced not only that body dissatisfaction is a potent component for the adoption of high-risk eating habits, but also that women face great social pressure regarding their weight and body shape.